2016
DOI: 10.1080/15384047.2016.1210740
|View full text |Cite
|
Sign up to set email alerts
|

Decursinol angelate inhibits PGE2-induced survival of the human leukemia HL-60 cell line via regulation of the EP2 receptor and NFκB pathway

Abstract: Decursinol angelate (DA), an active pyranocoumarin compound from the roots of Angelica gigas, has been reported to possess anti-inflammatory and anti-cancer activities. In a previous study, we demonstrated that prostaglandin E 2 (PGE 2 ) plays a survival role in HL-60 cells by protecting them from the induction of apoptosis via oxidative stress. Flow cytometry and Hoechst staining revealed that PGE 2 suppresses menadione-induced apoptosis, cell shrinkage, and chromatin condensation, by blocking the generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…In murine models of sepsis, HMGB1 is first detectable in the circulating blood 8 hours after the onset of the disease and subsequently reaches a plateau at 16 to 32 hours after onset. [8][9][10][11] As part of our ongoing research on the identification of novel lead compounds against Hutchinson-Gilford progeria syndrome (HGPS), we recently reported that JH-4, a synthesized decursin derivative, exhibits strong anti-HGPS activity by efficiently blocking progerin-lamin A/C binding. 7 Decursin, a class of linear dihydrocoumarins isolated from the root of Angelica gigas Nakai exhibits a number of physiological activities, including anticancer, antibacterial, neuroprotective, and antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…In murine models of sepsis, HMGB1 is first detectable in the circulating blood 8 hours after the onset of the disease and subsequently reaches a plateau at 16 to 32 hours after onset. [8][9][10][11] As part of our ongoing research on the identification of novel lead compounds against Hutchinson-Gilford progeria syndrome (HGPS), we recently reported that JH-4, a synthesized decursin derivative, exhibits strong anti-HGPS activity by efficiently blocking progerin-lamin A/C binding. 7 Decursin, a class of linear dihydrocoumarins isolated from the root of Angelica gigas Nakai exhibits a number of physiological activities, including anticancer, antibacterial, neuroprotective, and antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…I-κB inhibits NF-κBp65 from nuclear translocation and transcription of inflammatory genes [35]. But in case of liver injury or inflammation, I-κB is phosphorylated and degraded, thus resealing NF-κB where it activates downstream targets to regulate inflammatory gene transcription involved in HSC activation [36]. NF-κB activation has been noted in the HCC model of mice when injected with the carcinogens CCl4 and DEN [35,37].…”
Section: Discussionmentioning
confidence: 99%
“…The opening of Cx43-containing HCs has been associated with the suppression of breast cancer proliferation and metastasis [ 197 ]. In several cancers, the opening of HCs results in the release of significant amounts of PGE 2 , which regulates immune cell activation and protects lymphoblastic leukemia cells from other cells [ 198 , 199 ]. These results indicate that the opening of HCs also promotes the survival and metastasis of cancer cells.…”
Section: Connexin Channels: Novel Roles In Cancermentioning
confidence: 99%